BUDAYA DAN SENI TATO PADA PEREMPUAN SEBUAH INTERPRETASI KETIMURAN - Savitri, Intan Dewi (Studi Budaya Nusantara, 2017)
ABSTRACT The aim of this research is to describe the attitude towards women who choose to modify her body as a way to express herself, and the form chosen is what scholars may devine as body ink or tattoo. Learning from a study conducted by students from one of the university overseas that recently tattoo is becoming more popular, on the other hand, the stigma social attached to it, and therefore to the women wearing them, remains. Tattoo considered more mainstream these days, but not quite. As for method employed in this research, qualitative has been chosen, and in relation to that, also descriptive. Intervieuw utilizing questionnaire was employed in data collecting with Brawijaya University's students as participants. As a result, the majority of the participants submitted a negative answer that describe perception in relation to tattoo on women. Their opinion was supported first by stigma social holds against these women, secondly by the fact that tattoos are forbidden practice according to the teaching of a certain religion.